1998
DOI: 10.1063/1.120943
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional hysteresis behavior in compositionally graded Pb(Zr,Ti)O3 thin films

Abstract: Thin-film lead–zirconate–titanate (PZT) capacitors with composition gradients normal to the substrate were fabricated via a novel technique using pulsed laser deposition. These capacitors exhibited large polarization offsets when driven by an alternating electric field. The direction of the offsets depended on the direction of the gradient with respect to the substrate. The largest offset, greater than 400 μC/cm2 when driven with a 50 V/μm field, was nearly an order of magnitude greater than any reported for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 8 publications
3
58
2
Order By: Relevance
“…A composite possesses effective dielectric and ferroelectric properties, and we imagine this ''effective'' sample is placed in the Sawyer-Tower circuit. Figure 5 ϩ (sat) generally obeys a power law, 30,34,35 i.e., D o f f (sat)ϰE A ϩ (sat) n , 2ՇnՇ5, which differ from the present results. The possible reason is that, in our calculation, f ϩ and f Ϫ are assumed to be constants independent of E A ϩ (sat).…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Cocontrasting
confidence: 57%
See 1 more Smart Citation
“…A composite possesses effective dielectric and ferroelectric properties, and we imagine this ''effective'' sample is placed in the Sawyer-Tower circuit. Figure 5 ϩ (sat) generally obeys a power law, 30,34,35 i.e., D o f f (sat)ϰE A ϩ (sat) n , 2ՇnՇ5, which differ from the present results. The possible reason is that, in our calculation, f ϩ and f Ϫ are assumed to be constants independent of E A ϩ (sat).…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Cocontrasting
confidence: 57%
“…However, the drift magnitude might be surprisingly large and was reported to be an order larger than the spontaneous polarization. [33][34][35] Although our model assumes a single ferroelectric sample, our analysis is thought to be roughly valid for a graded ferroelectric, which is a multilayered composite. A composite possesses effective dielectric and ferroelectric properties, and we imagine this ''effective'' sample is placed in the Sawyer-Tower circuit.…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Comentioning
confidence: 99%
“…This is also the range of experimental measurements where notable vertical shifts of the hysteresis loop are reported in the literature. [12][13][14][15] In our previous study of compositionally graded ferroelectric films, we have already demonstrated that the polarization gradient across a ferroelectric film can lead to asymmetric conduction, which we believe provides a mechanism for the polarization offset phenomenon. Now it is worth further examining the asymmetric conduction current.…”
Section: B Effect Of Charge-carrier Mobilities and Film Thicknessmentioning
confidence: 99%
“…Indeed, many large polarization offsets observed in graded ferroelectrics possessed unequal shift magnitudes for downgraded and upgraded films. 29 Concerning the origin of asymmetric f , Bouregba et al suggested that the compositional gradient in a graded ferroelectric might induce some change in the free-carrier concentration and the magnitude of the band gap along the growth direction. 17 Those could lead to asymmetric conductivity within the film.…”
Section: Asymmetric Conductivity Induced Phenomenon Of Vertically mentioning
confidence: 99%